An Investigation into the Frequency and Patterns of Science Reporting in Three Leading Online Nigerian Newspapers from 2016-2022 - Matyek, Jimme; Maimoko, Dongvel Dorothy; Ochai, Thomas Odoh (Journal of Sociology: Bulletin of Yerevan University, 2023)
This study conducts a comprehensive seven-year analysis of science reporting in three prominent Nigerian online newspapers: Vanguard, Daily Sun, and Punch, spanning from 2016 to 2022. Research conducted before has shown that science journalists in Africa face difficulties. These challenges include editors who do not provide enough support and focus too much on politics, low salaries, and not having enough resources to do their work effectively. They also face criticism from scientists for perceived shortcomings in education, interview preparation, reporting accuracy, and ethical concerns regarding payment for information. In view of this, the problem of this study is the need to understand and analyze the frequency and patterns of science reporting in Nigerian newspapers, specifically in Vanguard, Daily Sun, and The Punch, from 2016 to 2022. Utilizing descriptive research methods, the research scrutinizes the frequency of science reports and their percentage relative to general reports in each newspaper. The findings reveal variations among the newspapers, with Vanguard consistently featuring the highest number of science reports. Noteworthy fluctuations are observed from year to year, indicating potential shifts in editorial priorities or public interest in science-related topics. The study underscores the importance of enhancing science reporting efforts in online newspapers to foster scientific literacy and awareness among readers. It emphasizes the necessity of adapting reporting trends to align with evolving public interests and scientific advancements.